Pengaruh Pengendalian Internal terhadap Pencegahan Kecurangan dengan Moralitas Individu sebagai Variabel Moderasi - Mirza, Chafif; muslichah, muslichah (Universitas Muhammadiyah Metro, 2025)
This study examines at the effect internal control on fraud prevention using morality as a moderating factor. A total of 125 individuals were chosen as research samples, out of the 658 employees of Bank Negara Indonesia (Persero) in Regional Office 11 in Manado. Research shows that internal control has a negative effect on fraud prevention. The results of this research also show that individual morality can strengthen the effect of internal control on fraud prevention.